2010
DOI: 10.1002/hbm.20972
|View full text |Cite
|
Sign up to set email alerts
|

The envious brain: The neural basis of social comparison

Abstract: Humans have a drive to evaluate themselves by examining their abilities and outcomes in comparison to others. The present study examined the emotional and neural correlates of upward social comparison (comparison with those who have more) and downward social comparison (comparison with those who have less). Two experiments were conducted with volunteers in an interactive game of chance, in which a putative player won or lost more money than the participant. The results showed that even when participants lost m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 37 publications
11
111
0
4
Order By: Relevance
“…Our meta-analysis first identified a consistent involvement of the VS and vmPFC in downward comparison. Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our meta-analysis first identified a consistent involvement of the VS and vmPFC in downward comparison. Based on the role of these regions in reward processing [Carlson et al, 2011;Cromwell et al, 2005;McClure et al, 2004;Rushworth et al, 2011;Sescousse et al, 2015], our findings dovetail with the notion that downward comparison is experienced as rewarding [Bault et al, 2011;Dvash et al, 2010;Fliessbach et al, 2007]. Prior studies have shown the involvement of the VS in the processing of other types of social rewards, including good reputation [Izuma et al, 2008;Meshi et al, 2013] and social approval [Izuma et al, 2010].…”
Section: Discussionsupporting
confidence: 84%
“…Eight out of 28 contrasts contributed to the cluster in vmPFC (MDE 5 21.26%; 2MDE 5 35.87%) (Table III). Self-gain/other-lost > Self-lost/other-gain 12 Beyer et al [2014a] 40 Self-won/other-lost > Self-lost/other-won 12 Beyer et al [2014b] 41 Self-won/other-lost > Self-lost/other-won 3 Brunnlieb et al [2013] 15 Self-won/other-lost > Self-lost/other-won 25 Cikara et al [2011] 18 Favored team's success/rival team's failure > control 9 Delgado et al [2008] 17 Self-gain/other-lost > Self-lost/other-gain 5 Du et al [2013] 19 Self-won/others-lost > self-lost/others-won 12 Dvash et al [2010] 16 Relative gain > relative loss 6 Emmerling et al [2016] 15 Self-won/other-lost > Self-lost/other-won 9 Fareri and Delgado [2014] 18 Self-won/others-lost > self-lost/others-won: social > non-social 8 Fliessbach et al [2007] 33 Self-won/other-lost > self-lost/other-won 1 self-lost/other-lost 8 Fliessbach et al [2012] 64 Self-won/other-lost > self-lost/other-won 1 self-lost/other-lost 2 Haruno & Frith [2010] 52 Parametric analysis, positive correlation with absoluate differences between two peoeple (self > other) Baumgartner et al [2011] 32 disadvantageous outcomes > equal outcomes 17 Beyer et al [2014a] 40 Self-lost/other-won > Self-won/other-lost 7 Beyer et al [2014b] 41 Self-lost/other-won > Self-won/other-lost 5 Cikara et al [2011] 18 Favored team's failure/rival team's success > control 3 Civai et al [2012] 19 disadvantageous outcomes > equal outcomes 12 Corradi-Dell'Acqua et al [2016] 19 disadvantageous outcomes > equal outcomes 21 Emmerling et al [2016] 15 Self-lost/other-won > Self-won/other-lost 4 Fatfouta et al [2016] 23 disadvantageous outcomes > equal outcomes 18 Farmer et al [2016] 18 disadvantageous outcomes > equal outcomes 6 Feng et al [2016] 40 disadvantageous outcomes > equal outcomes 10 Fliessbach et al [2012] 64 disadvantageous outcomes > equal outcomes 1 Gospic et al [1983] 17 disadvantageous outcomes > equal outcomes 4 Gradin et al [2015] 25 disadvantageous outcomes > equal outcomes 10 Guo et al [2013a] 18 disadvantageous outcomes > equal outcomes 10 Guo et al [2...…”
Section: Primary Ale Meta-analysis Resultsmentioning
confidence: 99%
See 3 more Smart Citations